Assessing the validity and reliability of the Indonesian version of Patient-Reported Outcomes Measurement Information System (PROMIS) Global Health Scale v1.2 - Vitriana Biben; Farida Arisanti; Efi Fitriana; Erika Maklun; Vindy Margaretha Miguna; Nabilla Fikria Alviani (Health and Quality of Life Outcomes)
Abstract Background The assessment of Health-Related Quality of Life (HRQoL) is essential in clinical outcomes, focusing on the subjective perception of individuals regarding the physical, mental, and social aspects of health status. However, conducting a large-scale HRQoL assessment poses various challenges that necessitate the development of a non-burdensome instrument. One promising solution is adapting Patient-Reported Outcomes Measurement Information System (PROMIS) Global Health Scale v1.2 through translation, validation, and cross-cultural testing for non-English populations. Therefore, this study aimed to evaluate the validity and reliability of the Indonesian version of PROMIS Global Health Scale for comprehensive HRQoL assessment. Method This cross sectional study involved a total of 343 participants, comprising patients, caregivers, and residents of Physical Medicine and Rehabilitation. PROMIS Global Health Scale v1.2 was subjected to translation and cultural adaptation using the Functional Assessment of Chronic Illness Therapy (FACIT) method. Content validity was tested by five experts using the Scale-Content Validity Index (S-CVI), and structural validity was evaluated through Confirmatory Factor Analysis (CFA). Internal consistency and test–retest reliability were examined using Cronbach's Alpha and intraclass correlation coefficient (ICC), respectively. Result The Indonesian version of PROMIS Global Health Scale v1.2 showed strong validity and reliability. Content validity analysis produced a S-CVI/Universal Agreement of 0.90 with item analysis factor loading’s of > 0.3. Structural validity results were χ2/df (1.53), RMSEA (0.04), RMR (0.03), and CFI (0.99). The reliability results showed that Cronbach's Alpha for Global Physical Health (GPH) and Global Mental Health (GMH) was 0.61 and 0.77, respectively. Test–retest reliability assessment performed using intraclass correlation coefficients generated values of 0.72 for GPH (95% CI, [0.65,0.78])and 0.70 (95% CI [0.63,0.76]) for GMH. Conclusion The Indonesian version of PROMIS Global Health Scale v1.2 showed sufficient content validity, structural validity, internal consistency, and reliability, which supported the application of this tool for HRQoL assessment in clinical and research settings.